Administrative strategies of the principal on the academic performance of students in Public Secondary Schools in Imo State - Obinna, Ajuzie Cosmas (Journal of Professional Teacher Education, 2025)
This study examined staffing/staff development, provision of learning materials, and motivation of teachers as administrative strategies of principals on the academic performance of students in public secondary schools in Imo State. It employed a survey design. Three research questions were posed, while two hypotheses were formulated and tested at the 0.05 level of significance. Hypothesis one showed that there is no significant difference in the mean rating of the responses of principals and teachers on the examined staffing on students’ academic performance. The second hypothesis showed that there is no significant difference between the mean perception of principals and teachers on the examined staff development on the academic performance of students. The population comprised twenty-six thousand two hundred and eighteen (26,218) teachers, principals, and students from public secondary schools in the 270 secondary schools in Imo State, with a sample size of 2,870 teachers, principals, and students. Data were collected using the “Principals' Administrative Strategies and Students’ Academic Performance Questionnaire (PASSAPQ)," which was validated and had a reliability index of 0.92. Mean scores and z-test statistics were employed for data analysis. The study revealed that there was adequate staffing in Imo State. There was, however, no significant difference in the mean rating of the responses of principals and teachers on the impact of the provision of learning materials on students’ academic performance. Another finding of this study shows that staff development impacts the academic.